Ecological study of Paracoccidioides brasiliensis in soil: growth ability, conidia production and molecular detection - Tercarioli, Gisela Ramos [UNESP]; Bagagli, Eduardo [UNESP]; Reis, Gabriela Martins [UNESP]; Theodoro, Raquel Cordeiro [UNESP]; Gimenes Bosco, Sandra de Moraes [UNESP]; da Graca Macoris, Severino Assis [UNESP]; Richini-Pereira, Virginia Bodelao [UNESP] (Biomed Central Ltd., 2007)
Background: Paracoccidioides brasiliensis ecology is not completely understood, although several pieces of evidence point to the soil as its most probable habitat. The present study aimed to investigate the fungal growth, conidia production and molecular pathogen detection in different soil conditions.Methods: Soils samples of clayey, sandy and medium textures were collected from ground surface and the interior of armadillo burrows in a hyperendemic area of Paracoccidioidomycosis. P. brasiliensis was inoculated in soil with controlled humidity and in culture medium containing soil extracts. The molecular detection was carried out by Nested PCR, using panfungal and species specific primers from the ITS-5.8S rDNA region.Results: the soil texture does not affect fungus development and the growth is more abundant on/in soil saturated with water. Some soil samples inhibited the development of P. brasiliensis, especially those that contain high values of Exchangeable Aluminum (H+Al) in their composition. Some isolates produced a large number of conidia, mainly in soil-extract agar medium. The molecular detection was positive only in samples collected from armadillo burrows, both in sandy and clayey soil.Conclusion: P. brasiliensis may grow and produce the infectious conidia in sandy and clayey soil, containing high water content, mainly in wild animal burrows, but without high values of H+Al.